2022
DOI: 10.1002/admi.202101723
|View full text |Cite
|
Sign up to set email alerts
|

Governing Factors for Carbon Nanotube Dispersion in Organic Solvents Estimated by Machine Learning

Abstract: The insolubility of single‐walled carbon nanotubes (SWCNTs) in most common organic solvents has been the cause of a bottleneck in their practical utilization. Aqueous SWCNT inks containing amphiphilic surfactants are widely used for processing including coatings and composite fabrication. Most practical processes are, however, designed to be compatible with organic solvents, generating a technological mismatch between production and utilization. This work reports on the surfactant‐assisted dispersion of SWCNTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Cellulosic polymers and some types of vinyl polymers have also been reported to aid in the colloidal dispersion of SWCNTs in arbitrary organic solvents. 34–36 A recent study based on artificial intelligence-assisted feature extraction suggested that weak interactions such as hydrogen bonding could be a key factor in the design of efficient surfactants. 36…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellulosic polymers and some types of vinyl polymers have also been reported to aid in the colloidal dispersion of SWCNTs in arbitrary organic solvents. 34–36 A recent study based on artificial intelligence-assisted feature extraction suggested that weak interactions such as hydrogen bonding could be a key factor in the design of efficient surfactants. 36…”
Section: Introductionmentioning
confidence: 99%
“…34–36 A recent study based on artificial intelligence-assisted feature extraction suggested that weak interactions such as hydrogen bonding could be a key factor in the design of efficient surfactants. 36…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have only been a few reports addressing complex systems, such as the fabrication of dispersions and interaction with other materials, where the dispersion outcome is inseparably governed by the fabrication factors. For example, Nonoguchi et al reported a ML study of the efficacy of various organic solvents for SWCNT dispersion using ethylcellulose as a dispersant . In addition, Nakada et al reported a ML model to analyze and predict new conditions for the efficient exfoliation of two-dimensional interlayer materials .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Nonoguchi et al reported a ML study of the efficacy of various organic solvents for SWCNT dispersion using ethylcellulose as a dispersant. 20 In addition, Nakada et al reported a ML model to analyze and predict new conditions for the efficient exfoliation of two-dimensional interlayer materials. 21 Furthermore, Glaubitz et al reported an attempt to determine the relationship between particle size and ultrasonic irradiation conditions in the liquid state using ML to ensure the reproducibility of ultrasonic treatment in nanoparticle dispersion.…”
Section: ■ Introductionmentioning
confidence: 99%